Optimizing Commitment - Tarigan, Azaria; Isa Indrawan, Muhammad (Proceedings of the International Conference on Multidisciplinary Science (INTISARI), 2024)
Support for facilities and infrastructure as well as adequate financial sources are other important elements in moving the wheels of an organization, but without the support of reliable human resources, organizational activities will not run, so optimizing the achievement of organizational goals cannot be achieved. This condition suggests that human resource development is an inevitable demand in order to ensure the availability of quality human resources according to organizational demands. The results of this research are as follows: Discipline has a positive and significant effect on Job Satisfaction with a value of 0.353 and a significant 0.012. Work Discipline has a positive and insignificant effect on Organizational Commitment with a value of 0.090 and a significant value of 0.323. Job Satisfaction has a positive and significant effect on Organizational Commitment with a value of 0.745 and a significant value of 0.000. Organizational Citizenship Behavior has a positive and significant effect on Job Satisfaction with a value of 0.557 and a significant 0.000. Organizational Citizenship Behavior has a positive and insignificant effect on Organizational Commitment with a value of 0.070 and a significant value of 0.301. Work Discipline has a positive and significant effect on Organizational Commitment through Job Satisfaction with a value of 0.263 and a significant value of 0.008. Organizational Citizenship Behavior has a positive and significant effect on Organizational Commitment through Job Satisfaction with a value of 0.415 and a significant value of 0.004.